Sex, physical activity, obesity, and hypercholesterolemia in millennial workers of X Corp, Jakarta, Indonesia, in 2023 - Yusvita, Fierdania; Nandra, Nadya Shinta (Universitas Gadjah Mada, 2023)
Purpose: This study aims to analyze the relationship between sex and sedentary behavior and obesity and its impact on hypercholesterolemia in millennial generation workers at X Corp., Jakarta, Indonesia, in 2023. Methods: This research is an observational analytic study conducted on 269 millennial workers at X Corp. The data collection used was the results of X Corp’s worker's medical check-ups. Data processing using the Chi-square test to see whether there’s a linkage between the research variables. Results: From the tables, there is a correlation found between sex and obesity (p=0.001); there is no correlation found between physical activity (p=0.105) and smoking behavior (p=1.000). There is a correlation between obesity and hypercholesterolemia (p=0.004) in millennial workers at X Corp. Conclusions: Unhealthy life behaviors can be a risk factor for health problems, including degenerative diseases, as millennial workers get older. Male workers are more at risk of being obese and having an impact on the emergence of hypercholesterolemia and the risk of diabetes mellitus if a healthy lifestyle is continuously neglected. It is suggested that the application of occupational health promotion at X Corp., Jakarta, Indonesia, can be further optimized.